Modular System Based on Interlocking Joints as a Circular Design Strategy for Coastal Community Buildings - Mega Vetra Salsabila; Kelik Hendro Basuki; Fadhilah Rusmiati (Fakultas Teknik Universitas Lampung, 2025)
Circular architecture promotes building systems that are efficient, adaptable, and responsive to the material life cycle. This research discusses the application of a modular system based on laminated bamboo interlocking joints as a circular design strategy for coastal community buildings, with a case study on the SAIBA Fishery Hub project in Kota Agung, Tanggamus Regency. The objective of this study is to identify the modular principles that support spatial flexibility and ease of maintenance, and to evaluate the effectiveness of interlocking joints in achieving construction efficiency and material sustainability. The research employs a qualitative descriptive method through literature review, field observation, and design synthesis. The findings indicate that the laminated bamboo interlocking system reduces construction waste and extends the lifespan of structural elements. Modular configuration enables flexible spatial adjustments according to dynamic coastal community activities such as training programs qnd communal space. Moreover, the use of locally sourced laminated bamboo minimizes carbon footprint and strengthens the identity of tropical coastal architecture. In conclusion, the modular system based on laminated bamboo interlocking joints represents an effective circular design strategy for sustainable, adaptable, and low-maintenance coastal community buildings.